The making of a modern Muslim woman : Begum Khurshid Mirza, 1918-1989 - Kazim, Lubna (Lahore : Brite Books, 2003)
On the life Begum Khurshid Mirza, a noted actress from Pakistan Television.
Keywords: Mirza, Begum Khurshid, -- 1918-1989.; Biographies